2004
DOI: 10.1111/j.1366-9516.2004.00078.x
|View full text |Cite
|
Sign up to set email alerts
|

Even population differentiation for maternal and biparental gene markers in Eugenia uniflora, a widely distributed species from the Brazilian coastal Atlantic rain forest

Abstract: Brazilian cherry (Eugenia uniflora L.) occurs in the Brazilian Atlantic Coastal Tropical Forest from the north‐eastern state of Ceara, to the southernmost state of Rio Grande do Sul. E. uniflora plays an important role in the maintenance of ‘Restinga’ ecosystems, at the interface between forest and strand vegetation. Here, we characterize the genetic diversity, its allocation within and between populations and the possible components of nuclear and cytoplasmic gene flow that determine the spatial distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 42 publications
5
29
0
8
Order By: Relevance
“…In accordance with our results, using expressed sequence tag simple sequence repeat markers, Rojas et al (2011) also found high levels of within population variation (80.3%) in Myrciaria dubia preserved at the Active Germplasm Bank in Manaus. Similar results were also reported based on microsatellite markers in other Myrtaceae species such as Melaleuca alternifolia with 93% and Eugenia uniflora with 78.9% (Rossetto et al, 1999;Salgueiro et al, 2004). According to Hamrick (1983), the distribution of genetic variation is not random within populations; instead, it is determined by the reproductive system, the geographical distribution, and the effective population size.…”
Section: Discussionsupporting
confidence: 69%
“…In accordance with our results, using expressed sequence tag simple sequence repeat markers, Rojas et al (2011) also found high levels of within population variation (80.3%) in Myrciaria dubia preserved at the Active Germplasm Bank in Manaus. Similar results were also reported based on microsatellite markers in other Myrtaceae species such as Melaleuca alternifolia with 93% and Eugenia uniflora with 78.9% (Rossetto et al, 1999;Salgueiro et al, 2004). According to Hamrick (1983), the distribution of genetic variation is not random within populations; instead, it is determined by the reproductive system, the geographical distribution, and the effective population size.…”
Section: Discussionsupporting
confidence: 69%
“…We expected this pattern because fragmentation has been recent relative to the generation time of these trees, and gene flow appears to be relatively high (N m = 5.23). Similar results of moderate differentiation have been found in other fragmented young Atlantic forest tree species (Seoane et al 2000, Auler et al 2002, Salgueiro et al 2004, Silva et al 2008). …”
Section: Saplingssupporting
confidence: 76%
“…Also, the relatively high gene flow (N m = 6.58) of the adults represents pre-fragmentation gene flow (Bossart & Prowell 1998). Indeed, outcrossing species generally demonstrate high levels of genetic variation within populations and lower genetic differentiation among populations (Loveless & Hamrick 1984), and similar results have been found in other fragmented Atlantic forest tree species (Seoane et al 2000, Auler et al 2002, Salgueiro et al 2004, Silva et al 2008.…”
Section: Adultssupporting
confidence: 63%
“…For the restinga plants studied in regard to morpho-physiological variations, we are not aware of the phenotypic integration of the various traits examined and therefore we know neither the spectrum of reaction norms (i.e., the set of phenotypes that can be produced by a given genotype exposed to distinct environmental conditions) that confer adaptation to these plants nor the genetic variation that promotes such responses. Genetic studies of restinga plants at the population or individual level are still in their infancy (e.g., Salgueiro et al 2004;Martins et al 2007) and shall be necessary to understand the role of genotypic variation vs. phenotypic plasticity in the process of adaptation from a rainforest habitat at their origin to open, coastal, oligotrophic conditions of the restinga (see also Pertoldi et al 2007).…”
Section: Acclimation or Stress Symptom?mentioning
confidence: 99%